Mechanism of action and therapeutic effects of oxidative stress and stem cell-based materials in skin aging: Current evidence and future perspectives - Qian, Huan; Shan, Yihan; Gong, Ruicheng; Lin, Danfeng; Zhang, Mengwen; Wang, Chen; Wang, Lu (Frontiers in Bioengineering and Biotechnology, 2023)
Aging is associated with multiple degenerative diseases, including atherosclerosis, osteoporosis, and Alzheimer’s disease. As the most intuitive manifestation of aging, skin aging has received the most significant attention. Skin aging results from various intrinsic and extrinsic factors. Aged skin is characterized by wrinkles, laxity, elastosis, telangiectasia, and aberrant pigmentation. The underlying mechanism is complex and may involve cellular senescence, DNA damage, oxidative stress (OS), inflammation, and genetic mutations, among other factors. Among them, OS plays an important role in skin aging, and multiple antioxidants (e.g., vitamin C, glutathione, and melatonin) are considered to promote skin rejuvenation. In addition, stem cells that exhibit self-replication, multi-directional differentiation, and a strong paracrine function can exert anti-aging effects by inhibiting OS. With the further development of stem cell technology, treatments related to OS mitigation and involving stem cell use may have a promising future in anti-skin aging therapy.